A Chlorzoxazone‐Baclofen Combination Improves Cerebellar Impairment in Spinocerebellar Ataxia Type 1. Issue 3 (5th November 2020) - Bushart, David D.; Huang, Haoran; Man, Luke J.; Morrison, Logan M.; Shakkottai, Vikram G.
ABSTRACT: Background: A combination of central muscle relaxants, chlorzoxazone and baclofen (chlorzoxazone‐baclofen), has been proposed for treatment of cerebellar symptoms in human spinocerebellar ataxia. However, central muscle relaxants can worsen balance. The optimal dose for target engagement without toxicity remains unknown. Using the genetically precise Atxn1 154Q/2Q model of spinocerebellar ataxia type 1, we aimed to determine the role of cerebellar dysfunction in motor impairment. We also aimed to identify appropriate concentrations of chlorzoxazone‐baclofen needed for target engagement without toxicity to plan for human clinical trials. Methods: We use patch clamp electrophysiology in acute cerebellar slices and immunostaining to identify the specific ion channels targeted by chlorzoxazone‐baclofen. Behavioral assays for coordination and grip strength are used to determine specificity of chlorzoxazone‐baclofen for improving cerebellar dysfunction without off‐target effects in Atxn1 154Q/2Q mice. Results: We identify irregular Purkinje neuron firing in association with reduced expression of ion channels Kcnma1 and Cacna1g in Atxn1 154Q/2Q mice. Using in vitro electrophysiology in brain slices, we identified concentrations of chlorzoxazone‐baclofen that improve Purkinje neuron spike regularity without reducing firing frequency. At a disease stage in Atxn1 154Q/2Q mice when motor impairment is due to cerebellar dysfunction, orally administered chlorzoxazone‐baclofen improves motor performance without affecting muscle strength. Conclusion: We identify a tight relationship between baclofen‐chlorzoxazone concentrations needed to engage target and levels above which cerebellar function will be compromised. We propose to use this information for a novel clinical trial design, using sequential dose escalation within each subject, to identify dose levels that are likely to improve ataxia symptoms while minimizing toxicity. © 2020 International Parkinson and Movement Disorder Society